Department of Information Technology in Institute of Medicine - Vaidya, P (Journal of Institute of Medicine Nepal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Journal of Institute of Medicine, August, 2008; 30:2 1 The full text of this paper is available from the Journal of Institute of Medicine website